2018
DOI: 10.3390/e20120917
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cold Rolling on the Phase Transformation Kinetics of an Al0.5CoCrFeNi High-Entropy Alloy

Abstract: The solid state phase transformation kinetics of as-cast and cold rolling deformed Al 0.5 CoCrFeNi high-entropy alloys have been investigated by the thermal expansion method. The phase transformed volume fractions are determined from the thermal expansion curve using the lever rule method, and the deformed sample exhibits a much higher transformation rate. Two kinetic parameters, activation energy (E) and kinetic exponent (n) are determined using Kissinger-Akahira-Sunose (KAS) and Johnson-Mehl-Avrami (JMA) met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 36 publications
(47 reference statements)
0
5
0
Order By: Relevance
“…Figure 8 depicts the thermal expansion curve, which provides insights into the phase transition process occurring during Q&P. As the CRRR increases, the temperature of Ac1, representing the start of ferrite-to-austenite transformation, decreases continuously. This phenomenon can be attributed to the increased driving force for phase transformation due to the introduction of deformation energy storage through cold rolling [ 29 ]. The reduction in Ac1 temperature indicates a higher tendency for austenite formation with increasing CRRRs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 8 depicts the thermal expansion curve, which provides insights into the phase transition process occurring during Q&P. As the CRRR increases, the temperature of Ac1, representing the start of ferrite-to-austenite transformation, decreases continuously. This phenomenon can be attributed to the increased driving force for phase transformation due to the introduction of deformation energy storage through cold rolling [ 29 ]. The reduction in Ac1 temperature indicates a higher tendency for austenite formation with increasing CRRRs.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 9 depicts the microstructure at 830 °C/100 s, revealing a decrease in the size of austenite grains with increasing CRRRs. This observation can be attributed to the higher number of nucleation points present in the cold-rolled samples during the austenite transformation process [ 29 , 32 ]. As a result, the size of the austenite grains at high temperatures is reduced.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 4 exhibits the microstructures of ultrafine grains and/or nanostructured precipitates generated simply through cold deformation and annealing under different conditions (Guo et al, 2018;Gwalani et al, 2018;Shi et al, 2018;Hou et al, 2019;Wu et al, 2019;He et al, 2020). In the meantime, Wang et al (2018c) investigated the effect of cold rolling on the fcc to bcc transformation kinetics of the Al 0.5 CoCrFeNi HEA and concluded that pre-deformation induced defects could facilitate the nucleation and growth process during the phase transition compared with the as-cast sample.…”
Section: Thermo-mechanical Coupling Effect Microstructure Evolution Amentioning
confidence: 99%
“…It caused grain refinement as well as hardness and electrical conductivity increases (up to 20% and 14%, respectively). Furthermore, the solid-state phase transformation kinetics of as-cast and cold rolling deformed Al 0.5 CoCrFeNi HEAs have been investigated by Wang et al [ 32 ] using the thermal expansion method. Lightweight AlCrMoTi and AlCrMoTiV HEAs were designed by Kang et al [ 33 ] and they were confirmed as solid solutions with minor ordered B2 phases.…”
Section: Mechanical Behaviorsmentioning
confidence: 99%